2013
DOI: 10.1063/1.4775591
|View full text |Cite
|
Sign up to set email alerts
|

Communication: One third: A new recipe for the PBE0 paradigm

Abstract: We analyze the performances of the parameter-free hybrid density functional PBE0-1/3 obtained combining the PBE generalized-gradient functional with a predefined amount of exact exchange of 1/3, as recently discussed by Cortona [J. Chem. Phys. 136, 086101 (2012)]. The numerical results that we have obtained for various properties, such as atomization energies (G2-148 dataset), weak interactions (NCB31 dataset), hydrogen-bond length optimizations, and dissociation energies (HB10 dataset), and vertical excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 30 publications
1
89
0
1
Order By: Relevance
“…It is worth to mention that very recently a different λ-dependence has been proposed, leading to a different integer for n [29,30].…”
Section: Theoretical Framework 21 Generalities: Acm and Associated Fmentioning
confidence: 99%
“…It is worth to mention that very recently a different λ-dependence has been proposed, leading to a different integer for n [29,30].…”
Section: Theoretical Framework 21 Generalities: Acm and Associated Fmentioning
confidence: 99%
“…Indeed, recently it has been suggested that a fraction of 1/3 exact exchange should be used as the PBEbased hybrid functional. 75 In addition, screened hybrids such as the Heyd, Scuseria, and Ernzerhof (HSE) functional 76 might be more computationally efficient and accurate in some cases, although their effect on molecular-crystal lattice energies is largely unknown. It is likely that for many of the hydrogen-bonded systems the lattice energy could be tuned with differing amounts of exact exchange and/or screening, as different systems have different hydrogen-bond strengths and therefore de-localisation.…”
Section: Role Of Exact Exchangementioning
confidence: 99%
“…Whereas for hybrid (e.g. PBE0 [52] or PBE0-1/3 [53]) density functionals the excitation energies Ω are obtained following the standard formalism, which have been thoroughly benchmarked in last years [54,55], an additional correction is however needed for the case of double-hybrid (e.g. PBE0-DH or PBE-QIDH) models [56], with the form:…”
Section: Theoretical Detailsmentioning
confidence: 99%